The Influence of Hydrogen Flow Rate and Humidifier Temperature on Performance of a PEMFC with Ti-Co/C Catalyst - Nurmalina Adhiyanti; Dedi Rohendi; Muhammad Prima Utama; Nirwan Syarif; Addy Rachmat; Dwi Hawa Yulianti; Normah Normah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
This study explores the effect of hydrogen flow rate and humidifier temperature on the performance of the Membrane Electrode Assembly (MEA) using Ti-Co/C catalyst at the cathode and Pt/C at the anode in a single-cell Proton Exchange Membrane Fuel Cell (PEMFC). MEAs were fabricated by the spraying method and characterized using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) to determine their electrochemical surface area (ECSA) and conductivity. The results showed that the optimized ECSA value reached 8.38 cm2/g, and the electrical conductivity was 3.76 Ã— 10-8 S/cm. The best performance was achieved at a hydrogen flow rate of 100 mL/min and room temperature humidification. Under the hydrogen flow rate test, the maximum power density reached 0.364 mW/cm2, while in the humidifier temperature variation, a maximum power density of 0.375 mW/cm2Â was obtained at a current density 2.4 mA/cm2. These findings suggest that Ti-Co/C is a promising low-cost catalyst alternative to Pt and that operational conditions play a critical role in MEA performance